Non-suicidal self-injury in adolescents: a clinician’s guide to understanding the phenomenon, diagnostic challenges, and evidence-based treatments - Apicella, Massimo; Pontillo, Maria; Maglio, Gino; Di Vincenzo, Cristina; Della Santa, Giorgia; Andracchio, Elisa; Vicari, Stefano (Frontiers in Psychiatry, 2025)
Non-suicidal self-injury (NSSI) is a prevalent and complex behavior, particularly among adolescents. This review explores the definition, epidemiology, and clinical significance of NSSI, emphasizing its role as a risk factor for suicidal behavior and its association with emotional dysregulation. Empirical and theoretical transdiagnostic approaches of different origins have advanced our understanding of NSSI, highlighting the importance of underlying psychological processes such as impulsivity, negative affect, and maladaptive coping strategies, yet NSSI in specific clinical presentations (e.g. Ultra-High Risk State for psychosis, autism spectrum disorders, gender dysphoria) remains understudied and less understood. Despite its inclusion in the DSM-5-TR as a condition for further study, NSSI remains undertreated, posing significant challenges for mental health care systems. The review examines the relationship between NSSI and specific psychiatric comorbidities, not limited to mood disorders, underscoring the need for tailored interventions. Psychotherapeutic approaches, such as Cognitive Behavioral Therapy (CBT), Dialectical Behavior Therapy (DBT), and Mentalization-Based Therapy (MBT), have shown promise in reducing NSSI, though long-term efficacy and comparative outcomes require further investigation. Pharmacological treatments, while limited, should focus on managing comorbid conditions rather than directly targeting NSSI. Emerging interventions may offer some potential but need further development. By integrating biological, psychological, and social perspectives, clinicians and researchers can better understand and address the multifaceted nature of NSSI. Early identification, comprehensive assessment, and targeted interventions are essential to mitigate the impact of NSSI and improve outcomes for affected individuals.